Obesity Is an Independent Predictor of Poor Survival in Metastatic Breast Cancer: Retrospective Analysis of a Patient Cohort Whose Treatment Included High-Dose Chemotherapy and Autologous Stem Cell Support - A. von Drygalski; T. B. Tran; K. Messer; M. Pu; S. Corringham; C. Nelson; E. D. Ball (International Journal of Breast Cancer)
The purpose of the study was to identify predictors of long-term survival in metastatic breast cancer (MBC). A cohort of 96 patients, who received high-dose chemotherapy with autologous stem cell support (HD-ASCT) as part of their treatment, was analyzed. Percent long-term survival at 10 years was 24.5% (CI 17.2–34.9%) when metastasis was diagnosed and 14.4% (CI 8.7–23.9%) when MBC was diagnosed. Survival was impacted significantly by body mass index (BMI). Median overall survival from initial diagnosis or from time of metastasis for patients with BMIs ≤30 and >30 (obese) was 7.1 (CI 4.4–8.7) and 3.2 years (2.41–6.75), respectively, or 3.2 or 2.3 years (all 𝑃=0.02). Also, obesity was the only independent patient-related predictor of time to metastasis and of survival. While obesity is linked with poor outcomes in earlier stages of breast cancer, this has not been previously reported for MBC.